Web Platform for linking Community Forestry Information in the Gambia. Integrates quantitative and qualitative information for monitoring and planning - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
Under development. The information platform development will be completed once the database and the dashboard are in place in 2019